2021
DOI: 10.3390/biom11050653
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Potential Anti-Inflammatory Natural Compounds Targeting the p38 Mitogen-Activated Protein Kinase (MAPK): Implications for COVID-19-Induced Cytokine Storm

Abstract: Severely ill coronavirus disease 2019 (COVID-19) patients show elevated concentrations of pro-inflammatory cytokines, a situation commonly known as a cytokine storm. The p38 MAPK receptor is considered a plausible therapeutic target because of its involvement in the platelet activation processes leading to inflammation. This study aimed to identify potential natural product-derived inhibitory molecules against the p38α MAPK receptor to mitigate the eliciting of pro-inflammatory cytokines using computational te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 130 publications
(177 reference statements)
0
20
0
Order By: Relevance
“…The residues with energy values less than −5 kJ/ mol or greater than 5 kJ/mol are more likely to contribute to the overall binding free energies associated with the protein-ligand interactions ( Figure 7 and Supplementary Figure S3 ) [ 127 ]. Residues which contribute high positive energies are unfavourable for ligand binding, whereas residues that contribute highly negative energies are favourable for ligand binding [ 128 ]. The per-residue decomposition results suggested that residues located in pocket 1 including Leu249, Val294, Val314, Pro316, Pro318 and Val327 ( Table 1 ) could play critical roles in the binding mechanisms ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The residues with energy values less than −5 kJ/ mol or greater than 5 kJ/mol are more likely to contribute to the overall binding free energies associated with the protein-ligand interactions ( Figure 7 and Supplementary Figure S3 ) [ 127 ]. Residues which contribute high positive energies are unfavourable for ligand binding, whereas residues that contribute highly negative energies are favourable for ligand binding [ 128 ]. The per-residue decomposition results suggested that residues located in pocket 1 including Leu249, Val294, Val314, Pro316, Pro318 and Val327 ( Table 1 ) could play critical roles in the binding mechanisms ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The p38 mitogen-activated protein kinase (MAPK) pathway plays a critical role in the COVID-19 cytokine storm and has been proposed as a recognized therapeutic target ( Asiedu et al, 2021 , Grimes and Grimes, 2020 ). The p38 MAPK signaling pathway can be triggered by environmental factors and pro-inflammatory stimuli that significantly influence a range of physiological activities, such as immune and inflammatory responses ( Cuadrado and Nebreda, 2010 ).…”
Section: Cytokine Storm and Cellular Signaling Pathways Induced By Th...mentioning
confidence: 99%
“…Therefore, stimulation of NLRP3 inflammasome and NF-κB signaling pathway by SARS-CoV-2 viral proteins could be the causal relationship between Covid-19 severity and progression of HF. In addition, p38 mitogen-activated protein kinase (MAPK) is highly activated by SARS-CoV-2 and linked with Covid-19 severity and systemic complications such as HF and cytokine storm (Meijles et al 2020 ; Asiedu et al 2021 ).…”
Section: Covid-19 and Risk Of Heart Failurementioning
confidence: 99%